The effect of processing parameters on microstructure and mechanical properties of aluminium 6061 semisolid metal billet - Muhammad Faez, Mohamad Tajudin (2021)
This thesis presents the experimental works on the effects of the semisolid metal (SSM) processing parameters on the aluminium feedstock billets produced by the direct thermal method (DTM). The combinations of pouring temperatures were fixed at 640 °C, 660 °C, and 680 °C with holding times of 20 s, 40 s, and 60 s, respectively. Three samples were produced for each of the combinations. The SSM feedstock billets were prepared by using DTM, in which 6061 molten metal was poured into a cylindrical copper mould with a different combination of pouring temperature and holding time before being solidified into room temperature water. The porosity content, ultimate tensile st1rength, and Vickers hardness were examined for the feedstock billets after the DTM process. There were differences in density value for each sample which occurred between 2.527 g/cm3 and 2.701 g/cm3. Sample 6 with a pouring temperature of 660 °C and holding time of 60 s has the highest density value, which was 2.701 g/cm3. This indicated that sample 6 has the lowest porosity content within the feedstock billets. The tensile test results showed that the ultimate tensile test values were between 65.39 MPa and 146.797 MPa, while the Vickers hardness test values were between 65.85 HV and 86.5 HV. In the sample with pouring temperature slightly above the aluminium 6061 liquidus temperature, the porosity content had decreased; tensile strength and hardness values had increased. Sample 4 with a pouring temperature of 660 °C and holding time of 20 s produced globular and small grain size for the primary phase area, which was 2547.87 µm2. Results show that, due to the rapid cooling condition of the molten 6061 inside the copper mould, more globular microstructures were obtained. The faster the heat is convicted out from the molten alloy will retard the formation of dendritic microstructure, thus transforming it into globular microstructure for SSM processing. The lower pouring temperature enhances the formation of nucleation during the solidification process, thus producing more globular microstructure and smaller grain size. The findings of this experimental works enhance a better understanding of the behaviour of aluminium alloy 6061 SSM feedstock billets. These findings could lead to better information on the formability behaviour of aluminium alloy 6061, mainly in the manufacturing industry.